Design and fabricate pocket allen key machine / Raja Amirul Syauqat Raja Sazrin - Raja Sazrin, Raja Amirul Syauqat (2024)
The objective of this research is to fabricate a prototype of pocket allen key machine. By using a single DC motor, it is capable of transmitting the power needed to complete the assembly of an IKEA product. The pocket allen key machine has a big potential in today’s market due to the highly numbered of people buying IKEA products. The furnitures built by this famous company often use a hexagonal-head fastener to help lessen the possibilities of the buyers defecting their furnitures. Therefore, this project focus on helping them in needs of assembling the parts easily plus lowering the risk to damage those IKEA’s products. The pocket allen key machine provides the community a new product t o choose rather than having the only option of buying a cordless drill. The fabrication process includes measuring, cutting, and drilling. This pocket allen key machine is made of an easily recycled plastic. We want to raise the community’s awareness towards this lovely earth. To raise the standard, this project aims to help lowering the temperature of the earth. It is operated by a DC motor as f or the rotation of the chuck and allen key. The mot or will be low in power to help lessen the risk of defecting the furniture when the assembling process is ongoing. Some recommendations can be added as an initiative such as a three-way switch to control the direction of the rotation.